Kewenangan Badan Amil Zakat Nasional (Baznas) dalam mengelola Harta Warisan : Studi Surat Edaran (Sema) Nomor 1 Tahun 2022 - Ulum, Rofiqul; Darmawanti, Darmawanti; Khojir, Khojir; Inayah, Sirri Khairu (Bulletin of Community Engagement, 2024)
There have never been any implementing regulations regarding procedures for applying for an order in court for assets where there are no heirs. The emergence of Supreme Court Circular Letter (SEMA) Number 1 of 2022 which stipulates that BAZNAS and Baitul Mal can become applicants in the management of inheritance that has no heirs, giving Baitul Mal and BAZNAS legal standing in court. For this reason, it is important to carry out this research with the main problem being what is the legality of granting authority to the National Zakat Amil Agency in managing inherited assets where there are no heirs through the Supreme Court Circular Letter (SEMA) Number 1 of 2022? and What is the ideal concept for managing inherited assets where there are no heirs from the perspective of Islamic law? With a normative research model, this research is a literature study using statutory and conceptual approaches. Based on the results of this research, it shows that the legality of granting BAZNAS authority through SEMA Number 1 of 2022 is legally valid because it is in accordance with Article 79 of Law Number 14 of 1985 concerning the Supreme Court and Article 3 letter b of Law Number 30 of 2014 concerning Government Administration namely creating legal certainty, as well as the issuance of Supreme Court Circular Letter (SEMA) Number 1 of 2022, an effort by the Supreme Court to provide legal protection when there are cases of inherited property where there are no heirs and to fill legal gaps or unclear regulations when there are cases of inherited property. which have no heirs and BAZNAS needs to make regulations regarding procedures for managing inherited assets that have no heirs because currently inherited assets that have no heirs are still managed as one with votive assets, trust or entrusted assets, sacrifices, kafarat, fidyah, grants, and confiscated assets which are called other religious social funds. Meanwhile, in terms of allocation, it is in accordance with Islamic Law which focuses on the benefit/welfare of the ummah. Keywords: Badan Amil Zakat Nasional, Inheritance, Managing Inheritance Assets